2014
DOI: 10.1016/j.jmmm.2013.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity, antiferromagnetism, and neutron scattering

Abstract: High-temperature superconductivity in both the copper-oxide and the iron-pnictide/chalcogenide systems occurs in close proximity to antiferromagnetically ordered states. Neutron scattering has been an essential technique for characterizing the spin correlations in the antiferromagnetic phases and for demonstrating how the spin fluctuations persist in the superconductors. While the nature of the spin correlations in the superconductors remains controversial, the neutron scattering measurements of magnetic excit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
2
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 195 publications
(279 reference statements)
1
111
2
2
Order By: Relevance
“…In copper oxide superconductors, superconductivity can only be induced by electron and hole doping into the nearly perfect CuO 2 plane, and impurity substitution at the Cu sites by other elements dramatically suppresses superconductivity (Armitage et al, 2010;Fujita et al, 2012;Kastner et al, 1998;Kivelson et al, 2003;Tranquada et al, 2014). The situation is much different for iron pnictides.…”
Section: Static Antiferromagnetic Order and Its Doping Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In copper oxide superconductors, superconductivity can only be induced by electron and hole doping into the nearly perfect CuO 2 plane, and impurity substitution at the Cu sites by other elements dramatically suppresses superconductivity (Armitage et al, 2010;Fujita et al, 2012;Kastner et al, 1998;Kivelson et al, 2003;Tranquada et al, 2014). The situation is much different for iron pnictides.…”
Section: Static Antiferromagnetic Order and Its Doping Evolutionmentioning
confidence: 99%
“…For copper oxides, superconductivity can be induced by charge carrier doping (electrons or holes) into the CuO 2 , resulting complicated phase diagrams with many incipient states competing with superconductivity (Armitage et al, 2010;Fujita et al, 2012;Kastner et al, 1998;Kivelson et al, 2003;Tranquada et al, 2014). The undoped copper oxides such as La 2 CuO 4 (Vaknin et al, 1987) and YBa 2 Cu 3 O 6+x (Tranquada et al, 1988) are simple antiferromagnets with the neighboring spins oppositely aligned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the dramatic differences in the ground states of their parent compounds and the microscopic origins of magnetism in different families of unconventional superconductors, inelastic neutron scattering experiments have revealed that superconductivity induces a collective magnetic excitation, termed neutron spin resonance, near the antiferromagnetic (AF) ordering wave vector of their parent compounds [4][5][6][7][8] . Experimentally, the resonance occurs at an energy E r and enhances dramatically below T c like the superconducting order parameter.…”
Section: Introductionmentioning
confidence: 99%
“…This notation implies a pseudotetragonal unit cell that is both convenient and appropriate given the relatively small orthorhombicity present in these materials [16][17][18][19] . The quasi-2D spin excitations are also known to be highly dispersive and to extend to energies ∼ 200 -300 meV depending on the precise level of doping [20][21][22][23] . Recent time-of-flight neutron scattering on lightly doped, x = 0.035, non-superconducting LBCO has revealed very interesting resonant enhancement of the magnetic spectral weight as a function of energy, that is co-incident with the low energy crossings of the highly dispersive spin excitations with weakly dispersive optic phonons 19 .…”
Section: Introductionmentioning
confidence: 99%